2016
DOI: 10.1186/s13071-016-1411-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and genetic characterisation of Acanthamoeba spp. from environmental and domestic water sources in Queen Elizabeth Protected Area, Uganda

Abstract: BackgroundAcanthamoeba is an emerging potentially pathogenic amoeba that has been receiving increasing attention worldwide as a reservoir and potential vector for the transmission of pathogenic bacteria. It is also associated with brain cell damage, keratitis and skin irritation in humans. Its effects are more severe in immunocompromised individuals. This study provides for the first time in Uganda, information on the prevalence and genotypes of Acanthamoeba in environmental and domestic (tap) water.MethodsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In another study about the distribution of Acanthamoeba genotypes in water samples from mineral water bottles in Porto Alegre, southern Brazil, the authors reported genotype T5 as the most common among the sequences analyzed [60]. Finally, Sente et al (2016) [61] reported the isolation of Acanthamoeba in 36 domestic water sources (42.9%) in the Queen Elizabeth Protected Area, Uganda, including the genotypes T1, T2, T4, T5, T6 and T11. Even when Acanthamoeba genotype T5 is the second most frequent genotype isolated from environmental sources [1], there are few reports which correlate this genotype with a clinical case.…”
Section: Discussionmentioning
confidence: 97%
“…In another study about the distribution of Acanthamoeba genotypes in water samples from mineral water bottles in Porto Alegre, southern Brazil, the authors reported genotype T5 as the most common among the sequences analyzed [60]. Finally, Sente et al (2016) [61] reported the isolation of Acanthamoeba in 36 domestic water sources (42.9%) in the Queen Elizabeth Protected Area, Uganda, including the genotypes T1, T2, T4, T5, T6 and T11. Even when Acanthamoeba genotype T5 is the second most frequent genotype isolated from environmental sources [1], there are few reports which correlate this genotype with a clinical case.…”
Section: Discussionmentioning
confidence: 97%
“…The microbial safety of swimming pool water is highly questionable in countries with poor regulatory framework due to the many existing possible microbial contaminant pathways. Microbial contamination of swimming pools can occur through (a) faecal contaminated source water or direct defecation from swimmers, birds, and animals [4][5][6][7], (b) nonfaecal human shedding from vomiting, sneezing, mucous, spitting, or skin, (c) poor wastewater disposal [8], (d) microbial biofilm formation along piped water networks [9,10], (e) contaminated air, dust, soil, or rainwater [11,12], and (f) individuals with contagious diseases or infectious pathogens [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Unless the pool is cleaned and maintained and its water adequately treated, contamination may lead to a number of disease outbreaks such as gastroenteritis, conjunctivitis, keratitis, trachoma, otitis, cholera, dysentery, eczema, skin rashes, typhoid, dysentery, giardiasis, cryptosporidiosis, helminthiasis, cholera, hepatitis, rotavirus infection, salmonellosis, and central nervous systems associated diseases [3,[13][14][15][16][17][18][19][20][21][22][23]. The aetiologic agents of some of these diseases have been isolated from natural and domestic water sources in Uganda and are associated with devastating illnesses [9,10,24,25]. Not much has been studied about microbial contamination of swimming pool water in Uganda, but available data denotes the presence of Streptococcus and Escherichia coli [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free-living amoeba (FLA) of the genera Naegleria, Acanthamoeba, and Hartmannella have been associated with water-related illnesses, especially in developed countries found in America, Europe, and the Middle East [1][2][3][4]. In many parts of Uganda, there is dependence on environmental water for washing, recreation, drinking, cooking, and other domestic purposes [5]. However, in most cases, this water is used without treatment, an act which predisposes Ugandans to FLA infection [5].…”
Section: Introductionmentioning
confidence: 99%